A First Look on the New Halle Economic Projection Model - Sebastian Giesen; Oliver Holtemöller; Juliane Scharff; Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
In this paper we develop a small open economy model explaining the joint determination of output, inflation, interest rates, unemployment and the exchange rate in a multi-country framework. Our model - the Halle Economic Projection Model (HEPM) - is closely related to studies recently published by the International Monetary Fund (global projection model). Our main contribution is that we model the Euro area countries separately. In this version we consider Germany and France, which represent together about 50 percent of Euro area GDP. The model allows for country specific heterogeneity in the sense that we capture different adjustment patterns to economic shocks. The model is estimated using Bayesian techniques. Out-of-sample and pseudo out-of-sample forecasts are presented. – – In diesem Diskussionspapier wird ein Modell vorgestellt, das die jeweilige gesamtwirtschaftliche Entwicklung in den größten Ländern des Euro- Währungsgebietes im Kontext der weltwirtschaftlichen Lage abbildet. Dabei wird an entsprechende Arbeiten des Internationalen Währungsfonds (global projection model) angeknüpft. In der hier dargelegten Basisvariante werden zunächst drei Länder modelliert, nämlich die USA und aus dem Euro-Währungsgebiet Deutschland und Frankreich, die zusammen etwa 50 Prozent des Bruttoinlandsproduktes des Euro-Währungsgebietes ausmachen. Das Modell berücksichtigt länderspezifische Anpassungsprozesse bei ökonomischen Schocks. Das Modell wird mit Bayesianischen Methoden geschätzt, und Prognosen zu unterschiedlichen Zeitpunkten werden präsentiert und diskutiert.
urn:nbn:de:101:1-2010070639
Keywords: C32; C53; E37; 330; Multi-country model; Forecasting; Bayesian estimation; Mehrländermodell; Prognose; Bayesianische Ökonometrie; Mehr-Länder-Modell; Ökonometrisches Makromodell; Wirtschaftsprognose; Konjunkturprognose; Prognoseverfahren; Eurozone; Deutschland; Frankreich; USA